Electromyographic Activation and Co-contraction of the Thigh Muscles During Pilates Exercises on the Wunda Chair - Panhan, Ana C.; Gonçalves, Mauro [UNESP]; Cardozo, Adalgiso C. [UNESP] (My University, 2023)
Objective: The aim of the present study was to investigate whether Pilates exercises on the Wunda chair (Going Up Front and Mountain Climb) activate the muscles rectus femoris (RF) and biceps femoris (BF) in 2 situations (foot on the pedal and foot on the seat). Methods: Sixteen young female Pilates practitioners (18-35 years old) participated in this study. The muscles of their right leg were then submitted to electromyography analysis during the exercises. Results: Significant differences were found for the RF muscle (maximal voluntary isometric contraction [%MVIC]), which was assessed and compared between the 2 exercises (Going Up Front and Mountain Climb: F = 9.83; P =.03; np2 = 0.14); 2 conditions (foot on the pedal and foot on the seat: F = 40.02; P <.001; np2 = 0.90) and interactions (F = 14.49; P <.001; np2 = 0.20) and for BF muscle (%MVIC) in the comparisons between the 2 conditions (foot on the pedal and foot on the seat: F = 27.5; P <.001; np2 = 0.82) and interactions (F = 12.57; P <.001; np2 = 0.17). The percentage of cocontraction presented the significant difference in the comparisons between the 2 conditions (foot on the pedal and foot on the seat: F = 24.07; P <.001; np2 = 0.286) Conclusion: Both Pilates exercises activated the thigh core muscles in the moderate and high categories. The highest percentage of cocontraction levels were presented when the foot was resting on the pedal.
Keywords: Electromyography; Exercise Movement Techniques; Kinesiology, Applied